Resistance memoirs of occupied France - Humbert, Agnes (Bloomsbury, 2009)
In the summer of 1940, as the German Occupation tightened its grip on Paris, Agnes Humbert helped to establish one of the first resistance cells. Within a year the group was publishing a news bulletin, helping allied airmen escape and passing military information back to London. Then came the catastrophe of betrayal, followed by arrest and interrogation, imprisonment and trial and, for Agnes, deportation to slave labour camp in Germany. Resistance is the secret journal of a woman who never gave up hope.